Natural Cellulose Fibers from Eulaliopsis Binata (Journal of Fiber Bioengineering and Informatics, 2014)
Natural cellulose fibers extracted from Eulaliopsis Binata (EB) were systematically investigated in thispaper. Fourier-transform infrared (FTIR), Scanning Electron Microscopy (SEM) and X-ray Diffraction(XRD) were used to investigate the chemical composition, morphological structure and crystallinestructure of the resulting fibers. Furthermore, some basic physical properties of the EB fiber, i.e.,mechanical properties, water absorption, antimicrobial performance were also evaluated and discussed.It was found that the non-cellulose substances were sufficiently removed or reduced after the degummingprocess, but the cellulose I structure was not changed based on the XRD and FTIR results. Meanwhile,the EB fibers exhibited high breaking strength (3.5 ∼ 6.9 cN/dtex) and remarkable moisture region(6.3 ∼ 7.7%). It also exhibited moderate antimicrobial effects against Escherichia coli. All these resultsindicated that the BP fibers had properties resembling those of traditional natural cellulose fibers (e.g.cotton and flax); therefore, they could be viewed as a promising alternative source for natural cellulosebundle fibers.